Bone Uptake of 99mTc-Phosphate via Labeled Plasma Protein - Schümichen, C.; Seifritz, R.; Hoffmann, G. (Nuklearmedizin - NuclearMedicine, 1980)
The transfer of albumin into the extravascular space of bone and other tissues was evaluated in the non-adult rat and was found to be less rapid in bone than in the liver and kidneys but more rapid than in muscle. Protein binding of 99mTc increased continuously with time after injection of 99mTc-EHDP and -PPi. One hour after administration, about 20% of the plasma activity of 99mTc-EHDP and 90% of 99mTc-PPi was bound to proteins. Thus the possibility exists that the fetation of 99mTc through protein binding in the extravascular space of bone contributes significantly to the regular bone uptake of 99mTc-phosphates, in the event that relatively unstable compounds such as 99mTc-PPi are used.